Pengelolaan Perancangan Sarana Prasarana Berbasis Lokal di Desa Pemo Kecamatan Kelimutu Kabupaten Ende melalui Kegiatan Kuliah Kerja Nyata Mandiri - Mikael Wora; Hendriko Dodi Ke; Mansuetus Gare (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
This article presents some of the main problems at the University of Flores 2021 Independent Real Work Lecture Location in the Pemo Village, Kelimutu District, Ende Regency. Partner needs: so that clean water can be reached in hamlet locations that have not yet been distributed clean water and every hamlet is required to have a clean water reservoir, in order to maintain a healthy environment so that garbage is not handed over, every hamlet is required to have a final waste disposal site and wants to have a website for marketing. Problems faced: Environment, Social, Technology and Clean water facilities. Methods of Implementation: lecture method, direct practice in mutual cooperation, evaluation after carrying out activities and suggestions for village government. The results of the activity: held discussions with village officials regarding the existing infrastructure in Pemo Village, had carried out Musrengbangdes activities at the village office, had carried out social service work every week at the village office location, village roads, and the hamlets in Pemo Village. Each hamlet already has a landfill, as well as creating a website for marketing local creative products, especially Tenun ikat. Community participation and support is quite high, where the community is active in implementing work programs so that what they want can be achieved and feel satisfied.